A Compartmentalized‐type Bifunctional Magnetic Catalyst for One‐pot Aerobic Oxysulfonylation and Asymmetric Transfer Hydrogenation. Issue 3 (25th November 2020) - Wang, Shitong; Wang, Chengyi; Lv, Ning; Tan, Chunxia; Cheng, Tanyu; Liu, Guohua
Abstract: Utilization of the confined cavity of the mesoporous silica, the exploration of the synergetic catalysis process for sequential organic transformations has great significance in asymmetric catalysis. In this study, the yolk‐shell‐structured magnetic nanoparticles with the chiral Ru/diamine species within the nanochannels of the outer mesoporous silica shell and the FeCl3 species on the inner magnet core are fabricated. The electron microscopy images and the structural characterizations disclose the uniformly distributed magnetic nanoparticles with the well‐defined single‐site ruthenium/diamine active centers onto the outer silica shell. As a yolk‐shell‐structured bifunctional magnet catalyst, the FeCl3 species enables an efficient aerobic oxysulfonylation between aryl‐substituted terminal alkynes and sodium sulfinates to the β‐keto sulfones intermediates, and the ruthenium/diamine species sequentially reduces the in‐situ generated intermediate to the chiral β‐hydroxysulfones products. As we envision, this one‐pot aerobic oxysulfonylation/asymmetric transfer hydrogenation process affords various chiral β‐hydroxysulfones in high yields with excellent enantioselectivities. Furthermore, this magnetic catalyst can also be conveniently recovered via an additional outer magnet and repeatedly recycled, showing a potential application in industrial interest. Abstract : Cascade to β‐hydroxysulfones : By integrating the chiral Ru/diamine and FeCl3 dual‐species into a yolk‐shell‐structured magnetic nanoparticles, this bifunctional catalyst enable an efficient aerobic oxysulfonylation/ATH cascade reaction of aryl‐substituted alkynes and sodium sulfinates process to afford various chiral β‐hydroxysulfones in good yields and excellent enantioselectivities.